Economic-State Variation in Uncertainty-Yield Dynamics - Connolly, Robert A; Dubofsky, David; Stivers, Chris (The Review of Asset Pricing Studies, 2021)
Abstract We show there is a much stronger negative, dynamic relation between changes in economic uncertainty and Treasury yields over weaker economic times since at least 1990. We document this economic-state variation in uncertainty-yield dynamics for weekly and monthly change horizons, for nominal yields and real-yield proxies, for multiple economic-state identification methods, and for different economic uncertainty metrics. We present additional findings that suggest short-term fluctuations in precautionary-savings and consumption-smoothing forces are more impactful on interest rate dynamics during weaker economic times, especially relying on surveys of expected economic growth and inflation. Received February 8, 2019; editorial decision August 24, 2020 by Editor Nikolai Roussanov. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.